The politics of natural resource investments and rights in Africa: A theoretical approach. Issue 3 (July 2020) - Buur, Lars; Pedersen, Rasmus H.; Nystrand, Malin J.; Macuane, José J.; Jacob, Thabit
Abstract: Over the past decade and a half, large-scale investments in natural resources in African countries have increased dramatically. While investments in natural resources and agriculture have become more important for African economies, since they have stimulated economic growth and made regimes dependent on rents and revenues for their own survival, surprisingly many investments fail to be implemented or fall through during implementation. Furthermore, natural resource investments often end up violating the rights of local populations, which can lead to severe social protests and political instability, as well as limiting the 'development' impact. In this article, we develop a theoretical approach focusing on the three-way relationship between investors, local populations and ruling elites and the wider context in which these relations are embedded. We argue that investments are more likely to be implemented and the procedural rights of local populations respected when relationships are characterized by 'reciprocal exchange deals' between investors and local populations, 'compatible interests' between ruling elites and investors, and 'mutual recognition' between local populations and ruling elites. We use eight examples of investments drawn from Mozambique, Tanzania and Uganda to explore the potential of this theoretical approach in explaining the circumstances in which the procedural rights of local populations are or are not respected and investments are or are not implemented.